Improving critical thinking capability through problem based learning models in islamic religious education subjects - Tohet, Moch.; Maulidiya, Wulan (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
This research aims to analyze the critical thinking capabilities of students through the Problem Based Learning (PBL) model in the context of Islamic Education (PAI). Critical thinking is an important skill that students need to possess in order to analyze, evaluate, and solve problems effectively. The PBL model at MA Nurul Jadid Peminatan Keagamaan program was chosen because it can encourage students to actively engage in the learning process, think critically, and apply religious knowledge in real situations. In this study, the data analysis used is the theory of Miles & Huberman which includes data reduction, data presentation, and concludes with drawing conclusions. Research results show that the application of the PBL model at MA Nurul Jadid in the Peminatan Keagamaan program significantly enhances students' critical thinking skills. This is evident from the improvement in their analysis, synthesis, and evaluation abilities in understanding the teaching material. Additionally, students also exhibit increased motivation and engagement in the learning process. The research findings indicate that the use of the PBL model as an effective strategy in Islamic education can improve students' critical thinking capabilities.